The broken children of Francoism. The experience of disability in a special education school run by the ANIC - Cayuela Sánchez, Salvador; Del Cura González, Mercedes (Historia y Memoria de la Educación, 2021)
Beginning at the end of the 1960s, the Franco regime promoted the creation of institutions and centres for the education and training of children and young people with disabilities. These entities, often dependent on private initiative, supplemented the lacking structure of services and benefits that Francoism had organized until then to deal with the problem of disability. In this paper we analyze the operation and the educational work developed in one of these centres during the last years of Franco’s regime and the first years of the democratic transition: the Special Education Center “Nuestra Señora de la Fuensanta” in Churra (Murcia). To this end, we have combined archival documentation with qualitative research methodologies, specifically 7 in-depth, semi-structured interviews, carried out both with former students and with members of the teaching and management team of the centre during our period of study. Through the memories and personal experiences of the interviewees, the article provides an account of their experience of disability and conveys the effects that the patients’ passage through the centre had on their lives.